The Role of Unilateral Spinal Anesthesia in Orthopedic Procedures in Elderly Patients (Texas Journal of Medical Science, 2022)
In patients in need of orthopedic surgery, it is very important and necessary to consider such patients during surgery and postoperative care, due to the significant anesthetic risk associated with significant aging and high comorbidity. In order to use anesthesia correctly, it is first necessary to have sufficient knowledge about intraoperative treatment (care) with possible complications in vital organs, adequate preoperative preparation, minimal physiological disturbances and side effects.